До питання необхідності проведення конституційної реформи в Україні в контексті децентралізації влади - Рудик, Петро Андрійович (My University, 2015)
Акцентується увага на чинниках, які зумовлюють потребу конституційної реформи в Україні на сучасному етапі її розвитку в контексті децентралізації влади: інтеграція України в європейську спільноту, врахування вимог сучасного етапу суспільно-політичного розвитку України, зміна підходів до визначення змісту реформи (впровадження європейських цінностей, принципів і норм європейських конституцій), необхідність подальшої демократизації українського суспільства та виконання Україною міжнародних зобов’язань і Мінських домовленостей. Розкривається активна участь Президента України і Верховної Ради у визначені такого процесу, дискусія між народними депутатами, громадськістю щодо окремих положень президентського законопроекту про внесення змін до Конституції України в частині децентралізації влади. Attention is focused on the factors that determine the need for constitutional reform in Ukraine at the present stage of its development in the context of decentralization of power: the integration of Ukraine into the European community, taking into account the requirements of the present stage of socio-political development of Ukraine, changing approaches to determining the content of the reform (introduction of European values, principles European constitutions and rules), the need for further democratization of Ukrainian society and Ukraine's fulfillment of international commitments and agreements Minsk. Expands the active participation of the President of Ukraine and the Verkhovna Rada by such a process, the debate between MPs, the public on certain provisions of the presidential bill on amendments to the Constitution of Ukraine in terms of decentralization.
Keywords: кафедра економіки і права; Конституція України; конституційна реформа; децентралізація влади; Constitution of Ukraine; constitutional reform; decentralization of power